2021
DOI: 10.1007/s11764-021-01094-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tandem cognitive behavioral therapy and healthy lifestyle interventions on health-related outcomes in cancer survivors: a systematic review

Abstract: Purpose Healthy lifestyle (HL) behaviors and cognitive behavioral therapy (CBT) have been individually shown to improve adverse effects of cancer treatment. Little is known about how such programs in tandem affect health-related outcomes. This review evaluates extant literature on tandem CBT/HL interventions on health-related outcomes in cancer survivors. Methods A comprehensive search of PubMed, PsychINFO, CINAHL, and Embase databases revealed numerous studies involving CBT and HL tandem interventions in canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…Interestingly, pain is one of the manageable risk factors for distress creating a problematic back loop because distress, in turn, promotes pain by dysregulating the autonomic, endocrine, and immune response [ 44 , 48 ]. This vicious cycle can be interrupted by cognitive behavioural stress management (CBSM) consisting of aspects of cognitive behavioural therapy (CBT) [ 49 , 50 , 51 ] or, more precisely, coping skills for stress management combined with relaxation training [ 45 , 52 , 53 , 54 ]. According to recent published systematic reviews and meta-analyses, CBT has a beneficial effect on cortisol secretion, distress, anxiety, depression, emotional well-being, and negative thoughts in CSs [ 49 , 50 , 51 ].…”
Section: State-of-the-artmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, pain is one of the manageable risk factors for distress creating a problematic back loop because distress, in turn, promotes pain by dysregulating the autonomic, endocrine, and immune response [ 44 , 48 ]. This vicious cycle can be interrupted by cognitive behavioural stress management (CBSM) consisting of aspects of cognitive behavioural therapy (CBT) [ 49 , 50 , 51 ] or, more precisely, coping skills for stress management combined with relaxation training [ 45 , 52 , 53 , 54 ]. According to recent published systematic reviews and meta-analyses, CBT has a beneficial effect on cortisol secretion, distress, anxiety, depression, emotional well-being, and negative thoughts in CSs [ 49 , 50 , 51 ].…”
Section: State-of-the-artmentioning
confidence: 99%
“…This vicious cycle can be interrupted by cognitive behavioural stress management (CBSM) consisting of aspects of cognitive behavioural therapy (CBT) [ 49 , 50 , 51 ] or, more precisely, coping skills for stress management combined with relaxation training [ 45 , 52 , 53 , 54 ]. According to recent published systematic reviews and meta-analyses, CBT has a beneficial effect on cortisol secretion, distress, anxiety, depression, emotional well-being, and negative thoughts in CSs [ 49 , 50 , 51 ]. Mindfulness-based stress reduction (MBSR) and yoga have also shown promising results on distress in CSs ( Figure 2 ) [ 52 , 53 , 54 ].…”
Section: State-of-the-artmentioning
confidence: 99%
“…Cancer is one of the world’s most incurable diseases and has the second highest mortality rate after cardiovascular disease ( 1 ). According to statistics of GLOBOCAN 2020, 19.3 million new cancer cases and almost 10 million cancer deaths were indicated in 2020.…”
Section: Introductionmentioning
confidence: 99%
“…However, this also brings with other aspects of problems. Long-term ongoing cancer treatment can take a huge physical toll and psychological burden on patients ( 1 ). Survivors may face months to years of cancer triggering and/or treatment-related symptoms such as fright of cancer recurrence, fatigue, insomnia, obesity, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Hersch et al showed that CBT reduced psychological pain, anxiety, and depression [ 19 ]. However, current studies on CBT intervention for cancer patients are mainly focused on breast cancer, followed by prostate cancer [ 20 ]. Few studies have been carried out on patients with gynecological malignant tumors.…”
Section: Introductionmentioning
confidence: 99%